Investigation of electrical, electromagnetic shielding, and usage properties of woven fabrics made from different hybrid yarns containing stainless steel wires - Bedeloğlu, Ayşe (Taylor & Francis Ltd, 2013)
This paper reports the results of a detailed study about specific properties of hybrid yarns and woven fabrics containing those yarns. For this aim, the fabrication procedures and physical properties of acrylic/stainless steel (SS) and cotton/acrylic/SS ply yarns were presented, and then, relations between those and electrical, electromagnetic shielding effectiveness (EMSE) and some usage properties of woven hybrid fabrics made from those with different constructions were investigated. EMSE of plain and twill fabrics were evaluated against radiating electromagnetic wave spectrum over a frequency 0-3000MHz. A comparison of physical properties of yarns regarding wire diameter and the use properties of fabrics regarding weave type, wire diameter, and yarn type measured were presented. The functional textile products of complex applications can be achieved with low cost, easily since those yarns and fabrics were produced on conventional textile manufacturing machines with small modifications. The present study indicated that use of SS wire-based yarns in fabrics significantly increased the air permeability, pilling resistance, thermal resistance, and the flexural rigidity of hybrid fabrics. The plain weave fabrics exhibited higher EMSE values over 20dB in higher frequencies and higher thermal absorbtivity values compared to twill fabrics.
Keywords: acrylic; hybrid yarn; electromagnetic shielding effectiveness; functional textile; hybrid fabric; hybrid yarn; stainless steel wire